My parent's keeper : the guilt, grief, guesswork, and unexpected gifts of caregiving - Gastfriend, Jody (Yale University Press, 2018)
"Unflinchingly tackles a complex aspect of eldercare in each chapter ... an indispensable resource for family caregivers."'Patrick O'Malley, author of Getting Grief Right When it comes time to provide care for those who once cared for us, where can we turn' This book offers practical guidance for a broad range of caregiving situations when family caregivers assume their new role. My Parent's Keeper ... Uses the latest research and draws on case histories and interviews. Is a resource as well as a source of inspiration, with a blend of powerful stories and practical advice. Helps caregivers cope with numerous challenges, including parents who need but refuse help; siblings who don't get along; the complexity of healthcare systems; financial issues; juggling work and caregiving; the use of technology; the power of connecting with a loved one who has dementia; and realizing the benefits amid the burdens of caregiving. "Jody Gastfriend has created the ultimate GPS for family caregivers. At once humane and helpful, personal and political, she charts the long, hard, and rewarding role that all of us will take caring for our families and each other. Don't leave home without it!"'Ellen Goodman, Pulitzer Prize-winning columnist and founder of The Conversation Project "My Parent's Keeper shines a light on the conundrum of caregiving'as adult children, our best intentions are insufficient to help our parents and ourselves. We need a plan in advance of need'this book offers up-to-date guideposts for this inevitable caregiving journey."'Laurie M. Orlov, author of When Your Parents Need Elder Care: Lessons from the Front Lines